Help Me: Evaluation of Applications to Support Women Victims of Domestic Violence - Oliveira, Cynthya Letícia Teles de; Ferrão, Isadora Garcia (Anais do Women in Information Technology (WIT), 2024)
Brazil, the fifth country with the most cases of femicide in the world, faces challenges both in its culture and in its public policies about supporting women who are victims of domestic violence. There are assistance programs, such as granting protective measures to ensure a minimum distance between the aggressor and the victim. Thus, different complementary initiatives emerged, such as applications that allow reporting incidents of violence and support for access. In this sense, this article proposes a technical evaluation of the five most popular brazilian applications on the Play Store dedicated to combating gender-based violence, considering technical metrics of usability and security.